STRENGTHENING MATERNAL AND CHILD PROGRAM IN INDONESIA THROUGH INTEGRATED PLANNING AND BUDGETING - Sutopo Patria Jati; Ayun Sriatmi; Martini Martini; Rani Tiyas Budiyanti; Nikie Astorina Yunita Dewanti; Nurhasmadiar Nandini; Budiyono Budiyono; Syamsulhuda B M (Journal of Public Health for Tropical and Coastal Region, 2020)
Background: Indonesia applies decentralization policy in health sector. However, there are Health Minimum Service Standards (HMSS) that must be met at provincial and district level. In district level, there are 12 indicators that must be achieved include of maternal and child health with the coverage must be 100%. Nevertheless, there are various problems in achieving HMSS both quantity and quality aspect. This study aimed to determine the problems that were happened and determine alternative solutions in the implementation of HMSS especially in maternal and child sector.Methods: This research was done in three steps. The first step was conducted by Focus Group Discussion (FGD) with participant from many stakeholders in Central Java and Yogyakarta. This step aims to identify problems in the implementation of HMSS and develop the alternative solution. Second stage was developing the conceptual framework.Results: Based on the research, there are many problems in quantitative and qualitative aspects related to healthcare services. Program planning and budgeting is the main key to achievement HMSS. In second and third steps, an integrated planning and budgeting framework between multisector was obtained including problem identification, problem cause analysis, multisector identification, setting solutions and programs, planning and budgeting, and monitoring and evaluation. So that, there were no overlapping programs, less optimal, and lack of supervision and guidance.Conclusions: Integrated planning and budgeting was alternative solution to solve the implementation problem in HMSS especially in maternal and child aspect. However, strong commitment and monitoring was needed between stakeholder.